1990
DOI: 10.3181/00379727-194-43055
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Soluble Form of Testis Adenylate Cyclase by Catechol Estrogens and Other Catechols

Abstract: The soluble form of rat germ cell adenylate cyclase was inhibited by compounds with a catechol moiety. Among the naturally occurring catechols tested, catechol estrogens were the most potent inhibitors. Catechol estrogens at 2-6 microM inhibited enzyme activity by 50% and almost completely at 30-100 microM concentration. The inhibitory activity of catechol estrogens depends on the catechol moiety of the molecule. Catechol per se also inhibited the activity of this enzyme, 50% inhibition being achieved at about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…Curiously, norepinephrine induced sperm capacitation at 3.1 lM and inhibited sperm capacitation at 3.1 mM [20]. Other findings suggest that catecholamines inhibit the soluble form of testis adenylate cyclase and propose that the high-concentration effect may be mediated by cytosolic catechols [47].…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, norepinephrine induced sperm capacitation at 3.1 lM and inhibited sperm capacitation at 3.1 mM [20]. Other findings suggest that catecholamines inhibit the soluble form of testis adenylate cyclase and propose that the high-concentration effect may be mediated by cytosolic catechols [47].…”
Section: Discussionmentioning
confidence: 99%
“…This study has addressed this question employing the following compounds: 2-Hydroxyestradiol (2OHE2) -Catechol oestrogens are major products of oestrogen metabolism in the testes. These steroid metabolites are known to have disruptive effects on the germinal and epididymal epithelia as well as the male germ line, inhibiting soluble adenylyl cyclase, cross linking sperm chromatin and promoting ROS generation (Braun, 1990;Seegers et al, 1991a,b;Bennetts et al, 2008). Recent studies in breast tissue, where catechol oestrogens are thought to be involved in the aetiology of cancer (Okoh et al, 2011), have suggested that these compounds stimulate H 2 O 2 production from the mitochondria (Felty et al, 2005), making it a particularly good reagent for assessing methods purported to detect mitochondrial ROS production in spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Mammals have nine tmAC genes (ADCY1-9), which differ in their tissue and developmental expression as well as in some of their regulatory properties (Cooper, 2003;Hanoune and Defer, 2001 (Braun, 1974;Braun, 1975;Braun, 1990;Braun, 1991;Braun and Dods, 1975). This enzyme was termed 'soluble adenylyl cyclase' (sAC) because its activity is preferentially found in the cytosolic fraction, although some activity is also found associated with membranes.…”
Section: Discovery Of Mammalian Sacmentioning
confidence: 99%
“…*Author for correspondence (mtresguerres@ucsd.edu) 1999; Chen et al, 2000), following on from earlier reports of Mn 2+ -stimulated cAMP activity in rat testis homogenates (Braun, 1974;Braun, 1975;Braun, 1990;Braun, 1991;Braun and Dods, 1975). This enzyme was termed 'soluble adenylyl cyclase' (sAC) because its activity is preferentially found in the cytosolic fraction, although some activity is also found associated with membranes.…”
Section: Reviewmentioning
confidence: 99%